Informal Microenterprises in Senegal : Performance Outcomes and Possible Avenues to Boost Productivity and Jobs - Atiyas, İzak; Dutz, Mark A. (Washington, DC : World Bank, 2022)
This paper explores differences and similarities across formal and informal microenterprises in Senegal. It uses a new national sample of more than 500 firms, of which two-thirds are informal and over 95 percent are micro-size, employing five or fewer full-time employees. The analysis finds that formal firms have average performance outcomes that are in the range of three to five times higher than informal firms. Formal firms are also more likely than informal firms on average to possess “good” characteristics, namely assets and uses of digital technologies that are positively correlated with productivity, sales, exporting, and employment. Despite these average differences, informal firms are highly heterogeneous, with a sizable number similar to formal firms in terms of both performance outcomes and good characteristics: the share of informal firms in the top productivity and sales deciles having good characteristics is substantial, and one-third of all firms in the high-performance cluster based on a data-driven combination of the four performance variables are informal firms. Importantly, several characteristics that are correlates of better performance (being in the top two clusters) for informal firms are identical to those for all firms in the high-performance cluster: having electricity, having had a loan, and in terms of uses of digital technologies, having a smartphone and using a mobile phone to communicate with suppliers and customers. However, a sizable number of high-performance informal firms are lagging in terms of good characteristics. That roughly half of formal firms and no informal firm had a loan implies that it is possible to be in the top performance cluster even without having access to such formal financing. That over half of formal firms in the top cluster as well as in the top decile of productivity and sales use inventory control/point of sales software as a management tool while only one informal firm does is both indicative of the small number of informal firms that use these technologies and suggestive of the potential for performance improvements if such technologies were used more widely.